ASSESSMENT OF NUTRITIONAL STATUS OF 1-5 YEAR OLD CHILDREN IN AN URBAN UNION COUNCIL OF ABBOTTABAD - Lodhi, Hassam Saqib; Rehman, Mahmood -Ur-; Lodhi, Fahd Saqib; Wazir, Salim; Jadoon, Huma (Journal of Ayub Medical College Abbottabad, 2010)
Background: Malnutrition is one the major public health problem in developing countries. In Pakistan more than 38% of the children are under weight and stunted. The current study is being done to access the nutrition status of children of 6 months to 5 years in District Abbottabad. The objectives of the study were to determine the macronutrient deficiency both acute and chronic in children 1-5 years of age, and recommend appropriate interventions. Methods: A cross-sectional descriptive survey was conducted in an urban Union Council (UC) of District Abbottabad, with a sample size of 100, selected through simple random sampling. For data collection a questionnaire was designed. Results: According to height for age Z-score, out of 100 children studied, 80 were normal while 17 were stunted and 3 were severely stunted. According to weight for age Z score, 79 children were normal, 11 were underweight and 10 were severely underweight. According to weight for height Z-score, 83 children were normal while 13 were wasted and 4 were severely wasted. Conclusion: Macronutrient deficiency is prevalent in our children. Macronutrient and micronutrient deficiencies can also occur concomitantly. The nutritional deficiency affects our children since their embryonic lives. The nutritional deficiency makes children vulnerable to contract diarrhoeal diseases, acute respiratory infections and other infections that further compound the situation. Keywords: Malnutrition, Nutrition assessment, under-5 children, Anthropometry, wasting, stunting, urban Pakistan